The impact of physical training lessons organization for the health of primary school children. - Shuba Ljudmila Viktorovna (Kharkov National Pedagogical University, 2011)
Was introduced the question of using tennis in physical training lessons to rise the health level of primary school children. Displayed the positive dynamic of missing the academic hours during school years. 96 children aged 6 years old (48 in control and 48 in experimental groups) were involved into experiment. In the research the special interest was given for using the methods and concept, gadgetry, different sport equipment. Was proved the scientific evidence of the elaborated innovative method with using tennis in physical training lessons.